RELIGIOUS MOBILITY AND IDENTITY IN THE LIVES OF URBAN MUSLIM SOCIETY IN AUSTRALIA: AN ANATOMY OF RELIGIOUS PRACTICE - Wildani Hefni; Rizqa Ahmadi; Maslathif Dwi Purnomo (Akademika : Jurnal Pemikiran Islam, 2022)
This article discusses religious mobility in the lives of urban Muslim society in Australia by investigating organizational projects and religious practices. This paper uses ethnographic fieldwork consisting of in-depth interviews and hang-out in the organization meeting and gatherings among urban Muslim society in Australia. This paper argues that although urban Muslim society in Australia is associated with a Muslim minority, they contribute significantly to the development of Islamic education, Islamic altruism, and spirituality performance. Urban Muslim society in Australia demonstrates social sensitivity by establishing social institutions to show their embodied Muslim identity, such as Islamic Society of Melbourne Eastern Region (ISOMER) in Melbourne, Islamic Science and Research (ISRA) in Sydney, and Australian Sufi Association (ASA). They show their religious mobility as well as their religious practices as part of an agent of social change by promoting community engagement as an embodiment of social solidarity.